Pertumbuhan Gereja Di Masa Pandemi - Megawati Manullang (Institut Agama Kristen Negeri Tarutung, 2021)
Abstract:The Covid-19 pandemic has so far been increasingly rampant and has had a bad impact on everyone and has made it more difficult for the church to develop, but this article discusses how to develop the church properly during this pandemic. The church can help each other by providing assistance, the church can also still carry out worship every week using social media and so on. This paper also tells every church servant to continue carrying out their duties even during the pandemic. This paper also explains how the church can maintain good communication with each congregation so that they can fellowship with each other again through online. and explain the use of technology for church services. The research method in this paper is a qualitative method. Keywords: church growth; church; pandemicAbstrak:Pandemi Covid-19 sampai sekarang semakin merajalela dan berdampak buruk bagi setiap orang dan semakin menyulitkan gereja untuk berkembang, namun dengan tulisan ini yang membahasas bagaimana cara mengembangkan gereja dengan baik pada masa pandami ini. Gereja dapat saling menolong dengan memberi bantuan, gereja juga tetap dapat menjalankan ibadah setiap minggu dengan menggunakan media sosial dan lain sebagainya. Dalam tulisan ini juga memberitahu kepada setiap pelayan gereja agar tetap menjalankan tugas walaupun sedang masa pandemi. Dalam tulisan ini juga di jelaskan bagaimana gereja dapat tetap menjalin komunikasi dengan baik terhadap setiap jemaat agar bisa saling bersekutu lagi melalui daring. serta menjelaskan pemanfaat teknologi untuk pelayanan gereja. Metode penelitian dalam tulisan ini adalah metode kualitatif. Kata kunci: pertumbuhan gereja; gereja; pandemi